2005
DOI: 10.1021/jp0451795
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Molecular Nitrogen and Oxygen with Extraframework Cations in Zeolites with Double Six-Membered Rings of Oxygen-Bridged Silicon and Aluminum Atoms:  A DFT Study

Abstract: The interaction of N(2) and O(2) with extraframework cations of zeolite frameworks was studied by DFT, using the B3LYP method. The extraframework cation sites located in the vicinity of the double six-member rings (D6R) of FAU zeolites (SI, SI', SIII') were considered and clusters with composition (M(n)(+))(2/)(n)()H(12)Si(10)Al(2)O(18), M = Li(+), Na(+), K(+), Ca(2+), were selected to represent the adsorption centers. The cation sites SII in the center of single six-membered rings (S6R) were modeled by [M(I)H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
3
20
1
Order By: Relevance
“…3), we can also show that the O 2 molecule was not on the straight line with the O-H bond of the acid site. These findings are in agreement with the DFT results reported by Mikosch et al [31] who states that O 2 forms a bent structure.…”
Section: Brønsted Site Models [Si(oh)al] and Their Interaction With Ssupporting
confidence: 93%
See 1 more Smart Citation
“…3), we can also show that the O 2 molecule was not on the straight line with the O-H bond of the acid site. These findings are in agreement with the DFT results reported by Mikosch et al [31] who states that O 2 forms a bent structure.…”
Section: Brønsted Site Models [Si(oh)al] and Their Interaction With Ssupporting
confidence: 93%
“…In a recent study, interactions of O 2 and N 2 with extraframework cations of aluminosilicate materials were investigated using the B3LYP density functional by Mikosch et al [31]. They concluded that the N 2 adsorption complexes with the extraframework cations are linear, while those with O 2 are bent regardless of the extraframework cations location.…”
Section: Introductionmentioning
confidence: 99%
“…These cages enclose large supercages with a free diameter of 12.7 Å. The supercages are accessible via 12 membered-ring windows with a diameter of 7.4 Å [6,7]. The monovalent and divalent extra-framework cations preferentially occupy different crystallographic sites (Fig.…”
Section: Sample Characterizationmentioning
confidence: 99%
“…Adsorption capacity increases in inverse proportion to the size of the compensation cation, i.e. when K + cations are replaced by Na + cations or Na + cations are replaced by Li + cations [6][7][8]. The Si/Al ratio also has an influence and better results were obtained when Si/Al tends to 1 [3,9].…”
Section: Introductionmentioning
confidence: 99%
“…The cluster we choose consists of a sodalite cage and D6Rs, which extend the study by a large series of bare extraframework cations or the clusters limited to S6Rs (a single six-membered ring) or D6Rs [22][23][24]. One framework Si atom was replaced by aluminium and the charge was compensated for by a Li + cation.…”
Section: Computational Detailsmentioning
confidence: 99%